Risk of Biliary Tract and Pancreatic Cancer Following Obstructive Sleep Apnea Diagnosis: Analysis of a National Health Insurance Database - Marn Joon Park; Gyu Tae Kim; Seo Jun Kang; Kyung-Do Han; Jae Hoon Cho; Ji Ho Choi (Journal of Rhinology)
Background and Objectives Obstructive sleep apnea (OSA) has been associated with an increased risk of cancer in various organs. OSA is also linked to chronic inflammation in the biliary tract and pancreas, a well-established risk factor for carcinogenesis in these organs. However, its relationship with biliary tract and pancreatic cancers remains unclear and has been rarely investigated. Therefore, we aimed to evaluate whether OSA serves as an independent risk factor for these malignancies by analyzing a nationwide healthcare claims database in South Korea. Methods A retrospective cohort study was conducted using the Korean National Health Insurance Service (KNHIS) database. Adults aged ≥20 years who were newly diagnosed with OSA (ICD-10: G47.30) between 2007 and 2014 were identified and propensity score-matched (1:5) with controls based on age, sex, and comorbidities. Individuals with pre-existing cancer diagnoses were excluded. The primary endpoints were the incidence of overall cancer, biliary tract cancer (C23–C24), and pancreatic cancer (C25). Cox proportional hazards regression models were used to calculate hazard ratios (HRs), adjusting for demographic and clinical factors. Results A total of 1,191,444 individuals were included, comprising 198,574 patients diagnosed with OSA and 992,870 matched controls. OSA was associated with an increased overall cancer incidence (HR, 1.132; 95% confidence interval [CI], 1.097–1.169); however, it was not significantly associated with pancreatic cancer (HR, 0.941; 95% CI, 0.823–1.072) or biliary tract cancer (HR, 0.931; 95% CI, 0.751–1.142). Subgroup analyses stratified by sex and age revealed no statistically significant associations across these groups. Conclusion Our findings do not support OSA as an independent risk factor for biliary tract or pancreatic cancers.